Normal schools and initial training: a social, historical and complex web - Hernández Aragón, Magaly (2024)
Initial teacher education in Mexico and, in most of the world, has become one of the most recurrent topics in the field of educational research. The analysis and understanding of its constitution and development, demands to situate it as a social, historical, cultural and political construct. In this sense, this text develops a historical relational view between the articulation of teacher training colleges, the teaching profession and initial training. From this, it highlights the changes experienced in the configuration of Mexican teacher education, based on the same social and historical development, but also on the ideological positions that each government has adopted, the economic-political interests, as well as the same international demands; therefore, the power relations that are intertwined to give shape and content to the training processes of the teacher educators are evidenced.